Entertaining the Idea Shakespeare, Performance, and Philosophy - Gallagher, Lowell; Kearney, James; Lupton, Julia Reinhard (University of Toronto Press, 2020)
To entertain an idea is to take it in, pay attention to it, give it breathing room, dwell with it for a time. The practice of entertaining ideas suggests rumination and meditation, inviting us to think of philosophy as a form of hospitality and a kind of mental theatre. In this collection, organized around key words shared by philosophy and performance, the editors suggest that Shakespeare's plays supply readers, listeners, viewers, and performers with equipment for living.In plays ranging from A Midsummer Night's Dream to King Lear and The Winter's Tale, Shakespeare invites readers and audiences to be more responsive to the texture and meaning of daily encounters, whether in the intimacies of love, the demands of social and political life, or moments of ethical decision. Entertaining the Idea features established and emerging scholars, addressing key words such as role play, acknowledgment, judgment, and entertainment as well as curse and care. The volume also includes longer essays on Shakespeare, Kant, Husserl, and Hegel as well as an afterword by theatre critic Charles McNulty on the philosophy and performance history of King Lear.